Mad dogs - Muchamore, Robert (London : Hodder Children's, 2007)
The British underworld is controlled by gangs. When two of them start a turf war, violence explodes on to the streets. The police need information fast, and James Adams has the contacts to infiltrate the most dangerous gang of all. He works for Cherub. Cherubs are trained professionals, aged between ten and seventeen. They exist because criminals never suspect that kids are spying on them. For official purposes, these children do not exist.
Originally published in Great Britain 2007.
Keywords: Spy stories